On the Politics of Being Jewish in a Multiracial State - Brodkin, Karen (Anthropologica, 2022)
The 1911 fire in the Triangle Shirtwaist factory is part of the cultural repertoire with which Jews in the U.S. constitute themselves. Its telling has changed greatly in the last 50 years. Recent tellings suggest that it is performing identity work in the constitution of a progressive Jewishness, in relationship to issues of race and gender. In particular, by portraying Jewish women's identities in ways that emphasize social justice activism as Jewish, these tellings also give men a platform from which to rethink the repertoire of alternatives of Jewish masculinity embedded in the old stories.